(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article explores the critical need to establish a scientifically grounded and precise legal definition of corruption. The author argues that the ambiguity of the concept of “corruption” in both international and national legal frameworks hampers effective anti-corruption measures. The article examines the socio-legal essence of corruption, its key features, subjects and objects, its latent nature, and its legal implications. It emphasizes the necessity to classify and legally demarcate corruption-related crimes accurately. A modular classification is proposed, based on criteria such as subject, object, form, and legal consequence. Additionally, the author suggests an evolutionary legal approach whereby normative classifications are periodically updated every 2–3 years based on expert monitoring and scientific analysis. This comprehensive legal and theoretical approach aims to enhance the efficacy of corruption prevention and law enforcement practices.